A prime decomposition algorithm for supercodes - Kieu, Hung Van (Journal of Computer Science and Cybernetics, 2013)
Supercode, a particular case of hypercodes, has been introduced and considered by D. L. Van and the author in previous papers. A supercode is called prime if it cannot be decomposed as a catenation of two supercodes. The prime decomposition of a supercode L is to decompose L into prime supercodes. In this paper, a linear-time prime decomposition algorithm for supercodes is proposed. The uniqueness of the prime decomposition for supercodes is presented.